Die psychotherapeutische Beziehung als Wirkfaktor Verknüpfung von Integrativer Gestalttherapie mit neurobiologischen Erkenntnissen - Begusch, David (e: Young Academics: Psychologie, 2023)
How and whereby does psychotherapy work and what influence do neurobiological factors have on its effectiveness? David Begusch combines neurobiological and immunological findings with findings from attachment and relationship research to work out and evaluate the effective factors of psychotherapy. By means of an extensive literature review, the author examines the relevance of the therapeutic relationship and then derives consequences for psychotherapy from neuroscientific findings. By combining concepts from both disciplines, he makes a groundbreaking contribution to the theoretical foundation of psychotherapy in general and Integrative Gestalt Therapy in particular.